In vivo ligation of linear DNA molecules to circular forms in the yeast Saccharomyces cerevisiae. - Suzuki, K (1983)
The yeast Saccharomyces cerevisiae was transformed with restriction endonuclease-digested (linear) DNAs containing the replication origin of the yeast 2 microns plasmid and selectable markers with efficiencies of 10(3) to 10(4), 10(3), and 10(2) to 10(3) transformants per microgram of DNA in the cases of transformations with linear DNAs containing the same cohesive ends, flush ends, and non-complementary cohesive ends, respectively. The results of a restriction analysis of the circular plasmids recovered from transformed cells suggested that the linear DNA molecules were ligated to produce circular forms in the recipient protoplasts.